Pengaruh Pemberian Edukasi Terhadap Pengetahuan Remaja Tentang Piper Crocatum Dalam Mengatasi Jerawat - Nurul Istiqomah; Ellyzabet Sukmawati; Sri Lestari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Acne is a common health problem experienced by adolescents, a skin disease found particularly in teenagers. Acne begins to emerge during puberty, and the main factors causing it are a lack of facial hygiene, excessive sebum production, clogged pores, and Propionibacterium acnes bacterial infection. The purpose of this study was to determine the effect of education on Piper crocatum in treating acne. This was a quasi-experimental study using a one-group pretest-posttest design. The population consisted of all 55 eleventh-grade students at Futuhiyyah Mranggen High School. Total sampling was used as the sampling technique. Data collection was done using pre- and post-questionnaires to assess the level of knowledge about Piper crocatum. Data were analyzed using the Wilcoxon test. The results showed a p-value of 0.00 (<0.05), indicating that there was an effect of providing education about Piper crocatum in treating acne in adolescents. The Z-value was -6.681, which means that the education about Piper crocatum had a significant effect, leading to an improvement in facial condition before and after the education was provided. In conclusion, providing education had a significant effect on the knowledge of adolescents about Piper crocatum in treating acne. The recommendation is that educating adolescents can increase their knowledge, understanding, and awareness of Piper crocatum as a treatment for facial acne.